2020
DOI: 10.3390/ijms21249725
|View full text |Cite
|
Sign up to set email alerts
|

The Cell-Free Expression of MiR200 Family Members Correlates with Estrogen Sensitivity in Human Epithelial Ovarian Cells

Abstract: Exposure to physiological estrogens or xenoestrogens (e.g., zearalenone or bisphenol A) increases the risk for cancer. However, little information is available on their significance in ovarian cancer. We present a comprehensive study on the effect of estradiol, zearalenone and bisphenol A on the phenotype, mRNA, intracellular and cell-free miRNA expression of human epithelial ovarian cell lines. Estrogens induced a comparable effect on the rate of cell proliferation and migration as well as on the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 82 publications
(81 reference statements)
8
30
0
Order By: Relevance
“…In our previous studies, we identified several cell-free miRNAs (e.g., miR-200 family members and miR-203a) as candidate biomarkers with good diagnostic parameters in ovarian cancer [9,10]. We also confirmed high cell-free miR-200s expression in estrogen sensitive epithelial ovarian cell cultures [11]. Here, we aimed to identify additional new miRNAs that might be used as future biomarkers in liquid biopsy.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…In our previous studies, we identified several cell-free miRNAs (e.g., miR-200 family members and miR-203a) as candidate biomarkers with good diagnostic parameters in ovarian cancer [9,10]. We also confirmed high cell-free miR-200s expression in estrogen sensitive epithelial ovarian cell cultures [11]. Here, we aimed to identify additional new miRNAs that might be used as future biomarkers in liquid biopsy.…”
Section: Introductionmentioning
confidence: 67%
“…We applied two cell lines that differed in the expression of Estrogen Receptor α (ERα); that receptor highly determined the expression of miRNAs in our previous studies [11]. The PEO1 highly expresses the Estrogen Receptor α (ERα) and proved to be estrogen sensitive in our previous studies [11]. The other cell line used was A2780 which does not express ERα and, as a result, does not respond to estrogen exposure, as it was shown previously [11].…”
Section: The Basal Expression Of Mir-205-5p and Let-7f-5p Is Higher Imentioning
confidence: 98%
See 3 more Smart Citations